Heart Rate Variability and Chronic Kidney Disease in Patients with Type 2 Diabetes - Wei Shi; Jing Zhang; Dan Chen; Xiaolei Chen; Wei Duan; Hongmei Zhang (Applied Bionics and Biomechanics)
To evaluate whether heart rate variability (HRV) as a measure of cardiac autonomic neuropathy (CAN) is associated with chronic kidney disease (CKD) in Chinese adults with type 2 diabetes mellitus (T2DM) in China. 392 individuals of T2DM were entered in this study, all these subjects undertook the Holter electrocardiogram for 24 hours to get the HRV parameters. Of these T2DM patients, 126 (37.3%) had CKD, and most of the HRV parameters were lower in this group than in those without CKD. Decreased HRV parameters were strongly related with CKD in Spearman’s correlation analysis. After adjustments for variables, the logistic regression showed that standard deviation of the averaged normal RR intervals for all 5-minute segments (SDANN) was independently associated with decreased estimated glomerular filtration rate (eGFR<60 mL/min/1.73 m2) (OR=0.988; 95% CI, 0.978-0.998; P=0.015) and increased urine albumin : creatinine ratio UACR≥30 mg/g Cr (OR=0.992; 95% CI, 0.985-0.998; P=0.015). A decreased 24-hour time domain HRV parameter, SDANN, was strongly associated with both eGFR and UACR among Chinese T2DM.